Farm productivity and farmers' welfare in West Timor, Indonesia - Benu, Fredrik Lukas (Curtin University, 2003)
This study examines agricultural productivity and farmers' welfare in West Timor, Indonesia. The driving force behind this study is to understand why the welfare of farmers has lagged behind others despite significant growth in the agricultural sector. The main research problem in this study is that while agricultural production has increased significantly in West Timor, the welfare of farmers has not increased as fast as that of non-farmers. To reduce the gap in income between farmers and nonfarmers, the growth of income of West Timor's farmers, as the indicator of their welfare, has to accelerate at least as fast as the growth of non-farmers' income. This target might be achieved if there is an appropriate policy of agricultural development implemented by the government. For this reason, evaluation of the structure of agricultural production, as well as the welfare of the farmers of West Timor, is an important issue that needs to be addressed. This study analyses the structure of agricultural production and the welfare of farmers in West Timor. An econometric method (Three Stage Least Squares) was used in modelling the agricultural system to evaluate the structure of the agricultural production as well as farmers' welfare in West Timor. A simultaneous equations model which consists of eight structural and four identity equations was constructed for the analysis of the structure, the estimation of elasticities from the regression coefficients and the subsequent policy analysis. The data used for the analysis are secondary data published by the Indonesian government.All data used in the model were time series data from 1979 to 1998 and gathered in the period between January and July 1999. The results of this research found that technical factors such as water availability. pasture capacity and irrigation channels influence the production of agriculture more than economic factors such as the price of products and cost of inputs. Too, population growth and the availability of socio-economic institutions such as cooperatives at the village level. have a significant influence on the agricultural production. Although technical factors influence the production of agriculture more than economic factors, subsequent policy analysis shows that an increase in agricultural credit as well as a reduction in the cost of production will still have a positive impact on the production of agriculture. A policy to increase the price of agricultural commodities at the farm gate, especially the price of live cattle and rice, will increase the profit of farmers, further motivating them to increase their overall production. There are six scenarios of the policy alternatives that are simulated in this study. These are: (1) the scenario of a 10 per cent increase in the size of irrigated areas, (2) the scenario of a 10 per cent increase in the amount of credit, (3) the scenario of a 35 per cent decrease in total cost per hectare of maize cultivation, (4) the scenario of a 10 units increase in the number of cooperatives, (5) the scenario of a 10 per cent increase in the price of live cattle at the farm gate, and (6) the scenario of a 10 per cent increase in the price of rice at the farm gate.The results of the policy analysis found that the largest positive impact on the agricultural sector output as well as farmers per capita income is derived from the scenario of a 10 per cent increase in the size of irrigated area. The scenarios of increasing amount of agricultural credit and the number of co-operatives have also generated a large positive impact on the agricultural sector output, but with a high increase in farmer population growth. Two other scenarios that have a large impact on the agricultural sector output as well as farmers' per capita income are the scenario of a 10 per cent increase in the price of live cattle and the price of rice. Based on the results of the policy analysis, two main policies that might be undertaken by the government to promote the growth of the agricultural sector and farmers' per capita income are expansion of irrigated areas and improving farmers' access to agricultural credit.